Status of woodland caribou in Saskatchewan - Rettie, Jim; Rock, Terry; Messier, Francois (Rangifer, 1998)
Recent research has shown that woodland caribou in Saskatchewan exist as relatively separate populations within a metapopulation. Preliminary analyses show that individuals within all populations are selecting peatland habitat types (i.e., fens and bogs) throughout the year. Despite an absence of hunting, populations south of the Precambrian shield appear to be declining slowly, while those on the southern margin of the shield may be declining more rapidly. The apparent population decline is likely due to high rates of predation, especially on neonates. To maintain viable caribou populations in the region, forestry operations must be managed to maintain adequate amounts of preferred habitat types and connections among populations. At a coarse scale, preferred habitat is that which acts as a refuge from predators. Additional information is required to categorize specific peatland types, as data in the existing provincial forest inventory are inadequate for both selection analysis and management purposes. Ongoing research into revisions to the forest inventory and analyses of bog and fen types selected by caribou are needed to focus future management strategies.